Risk factors for myopia in a discordant monozygotic twin study. (17th September 2015) - Ramessur, Rishi; Williams, Katie M.; Hammond, Christopher J.
Abstract Purpose Monozygotic (MZ) twin pairs discordant for disease allow careful examination of environmental factors whilst controlling for genetic variation. The purpose of this study was to examine differences in environmental risk factors in MZ twins discordant for myopia. Methods Sixty four MZ twin pairs discordant for refractive error were interviewed. Discordant twins were selected from 1326 MZ twin pairs from the TwinsUK adult twin registry with non‐cycloplegic autorefraction. Discordancy was defined as ≥2 Dioptres (D) difference in spherical equivalent (SphE) and discordant for class of refractive error. In a 35‐item telephone questionnaire twins were separately asked (and scored) about the risk factors urban/rural residence, occupational status and highest educational level. They responded with more (1), less (−1) or the same (0) as their twin on time spent outside, playing outdoor sport, and on close work aged <16 and 16–25 years. The lower SphE twin's score was subtracted from the higher SphE twin's score, and mean values of the difference calculated for each variable. Results Sixty four twin pairs were included (mean age 56, range 30–79 years; mean difference in refraction 3.35 D, S.D. 1.55 D, median difference 2.78 D). Within discordant MZ twin pairs, the more myopic twin was associated with having a higher occupational status (mean score between 16 and 25 years −0.11; 95% CI −0.19 to −0.04; mean score aged >25 years −0.23, 95% CI −0.28 to −0.17), being resident in urban area (mean score −0.26; 95% CI −0.33 to −0.18) and performing more close work (mean score <16 years −0.11; 95% CI −0.18 to −0.05; mean score aged 16–25 years −0.17, 95% CI −0.24 to −0.10) than their twin. The twins who spent more time outdoors (mean score <16 years 0.09; 95% CI 0.03–0.15; mean score aged 16–25 years 0.28, 95% CI 0.15–0.41) or performed more outdoors sports (mean score <16 years 0.13; 95% CI 0.04–0.21; mean score aged 16–25 years 0.23, 95% CI 0.10–0.36) were less likely to be myopic than their twin. Conclusions This study has confirmed known environmental risk factors for myopia. These data will allow selection of discordant twins for epigenetic analysis to advance knowledge of mechanisms of refractive error development.